High-performance speed control for three-phase induction motor based on reverse direction algorithm and artificial neural network - Al-Khawaldeh, Mustafa A.; Ghaeb, Jasim A.; Salah, Samer Z.; Alrawajfeh, Mohammad S. (International Journal of Electrical and Computer Engineering (IJECE), 2024)
This research proposes two approaches for determining the required frequency and modulation index for a pulse-width-modulation (PWM) system in a variable frequency drive (VFD) to control the speed of the three-phase induction motor. The first approach which is the reverse direction algorithm (RDA), uses a set of equations to calculate the necessary frequency and voltage for maintaining a constant motor speed under varying load conditions. The second one involves training a neural network (NN) on data collected by the RDA, which can then be used to continuously adjust the motor speed in real time to adapt to changing load torque requirements. Simulation and laboratory models for the three-phase induction motor are built and the proposed RDA-NN controller is examined. Results have proved that the proposed controller is effective in providing a stable and responsive motor speed control system.